2019
DOI: 10.1007/s12975-019-00744-5
|View full text |Cite
|
Sign up to set email alerts
|

Neurovascular Unit as a Source of Ischemic Stroke Biomarkers—Limitations of Experimental Studies and Perspectives for Clinical Application

Abstract: Cerebral stroke, which is one of the most frequent causes of mortality and leading cause of disability in developed countries, often leads to devastating and irreversible brain damage. Neurological and neuroradiological diagnosis of stroke, especially in its acute phase, is frequently uncertain or inconclusive. This results in difficulties in identification of patients with poor prognosis or being at high risk for complications. It also makes difficult identification of these stroke patients who could benefit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 214 publications
(274 reference statements)
0
54
0
1
Order By: Relevance
“…In ischemic stroke, diagnosis and the decision to proceed with intravenous and catheter-based reperfusion therapies are made by considering the severity of clinical deficits with the National Institutes of Health Stroke Scale (NIHSS), imaging studies such as non-contrast computed tomography (CT) and CT-based Alberta Stroke Program Early CT Score (ASPECTS) to assess for early ischemic changes, CT angiography to confirm intracranial proximal large vessel occlusion, and multimodal imaging with CT or magnetic resonance imaging (MRI) perfusion studies to estimate potentially viable brain tissue where appropriate [25,26]. Despite having teams specialized in cerebrovascular disease, stroke cases can generate diagnostic difficulties, and the diagnosis of acute ischemic stroke may be delayed in up to 30% of patients especially with subtle clinical findings [3,27]. In the diagnosis of cerebral ischemia associated with SAH and cardiac arrest, there are critical hurdles such as a mismatch between angiographic vasospasm and regional hypoperfusion, limited clinical evaluation in the setting of impaired consciousness, and toxic and metabolic confounders [16,17].…”
Section: Approaches To Diagnosis and Investigation Of Cerebral Ischemiamentioning
confidence: 99%
See 2 more Smart Citations
“…In ischemic stroke, diagnosis and the decision to proceed with intravenous and catheter-based reperfusion therapies are made by considering the severity of clinical deficits with the National Institutes of Health Stroke Scale (NIHSS), imaging studies such as non-contrast computed tomography (CT) and CT-based Alberta Stroke Program Early CT Score (ASPECTS) to assess for early ischemic changes, CT angiography to confirm intracranial proximal large vessel occlusion, and multimodal imaging with CT or magnetic resonance imaging (MRI) perfusion studies to estimate potentially viable brain tissue where appropriate [25,26]. Despite having teams specialized in cerebrovascular disease, stroke cases can generate diagnostic difficulties, and the diagnosis of acute ischemic stroke may be delayed in up to 30% of patients especially with subtle clinical findings [3,27]. In the diagnosis of cerebral ischemia associated with SAH and cardiac arrest, there are critical hurdles such as a mismatch between angiographic vasospasm and regional hypoperfusion, limited clinical evaluation in the setting of impaired consciousness, and toxic and metabolic confounders [16,17].…”
Section: Approaches To Diagnosis and Investigation Of Cerebral Ischemiamentioning
confidence: 99%
“…Given all these difficulties, timely availability of bedside diagnostic and prognostic tests based on panels of biomarkers would be useful information when managing patients with cerebral ischemia. Even with an increasing knowledge of cerebral ischemia, advances in imaging techniques, a better understanding of risk factors, and improvements in the treatment guidelines and organization of medical teams, timely and accurate diagnosis of cerebral ischemia remains challenging [3,16,17,20,[25][26][27][28][29][30]. Additionally, the sensitivity of non-contrast CT, CT angiography, and CT perfusion is highly variable [31].…”
Section: Approaches To Diagnosis and Investigation Of Cerebral Ischemiamentioning
confidence: 99%
See 1 more Smart Citation
“…BBB destruction is a common consequence of stroke, leading to severen complications, contributing to further development of cerebral ischemic injury [25]. BBB does not operate independently but as a multicellular neurovascular module of the NVU [4,26]. The BBB plays a pivot in the pathophysiology of IS.…”
Section: Discussionmentioning
confidence: 99%
“…Many clinical trials fail due to reduced neuroprotective effects in severely damaged blood vessels after IS [3]. A new research model of neuroprotection, consisting of neurons, vascular endothelial cells, astrocytes and phagocytes-neurovascular unit (NUV) [4], which focuses on the interaction between neurons, astrocytes, and capillaries, creating a new paradigm to understand the pathophysiology and drug development of stroke [5].As an essential part of the NVU, the BBB plays a vital role in IS pathophysiology Oxymatrine (OMT) is a quinazolidine alkaloid extracted from the traditional Chinese medicinal plant, Sophora avesicum (kushen), which has various pharmacological properties [6].OMT helps treat cancer, arthritis, chronic hepatitis, and other diseases [7][8][9], and can play a neuroprotective role in animal models of cerebral ischemia-reperfusion (cI/R) injury [10][11]. Studies have shown that OMT can battle against ischemic and hypoxic brain damage in rats caused by apoptosis and oxidative stress [12].…”
Section: Introductionmentioning
confidence: 99%